Fracture healing in HIV-positive populations. - Richardson, J; Hill, A; Johnston, C; McGregor, A; Norrish, A; Eastwood, D; Lavy, C (2008)
Highly active anti-retroviral therapy has transformed HIV into a chronic disease with a long-term asymptomatic phase. As a result, emphasis is shifting to other effects of the virus, aside from immunosuppression and mortality. We have reviewed the current evidence for an association between HIV infection and poor fracture healing. The increased prevalence of osteoporosis and fragility fractures in HIV patients is well recognised. The suggestion that this may be purely as a result of highly active anti-retroviral therapy has been largely rejected. Apart from directly impeding cellular function in bone remodelling, HIV infection is known to cause derangement in the levels of those cytokines involved in fracture healing (particularly tumour necrosis factor-alpha) and appears to impair the blood supply of bone. Many other factors complicate this issue, including a reduced body mass index, suboptimal nutrition, the effects of anti-retroviral drugs and the avoidance of operative intervention because of high rates of wound infection. However, there are sound molecular and biochemical hypotheses for a direct relationship between HIV infection and impaired fracture healing, and the rewards for further knowledge in this area are extensive in terms of optimised fracture management, reduced patient morbidity and educated resource allocation. Further investigation in this area is overdue.